HOW TO GET BOOKS IF YOU WERE A LUTHERAN PRIEST IN FINLAND OR EAST PRUSSIA IN THE 18TH CENTURY: PRIVATE LIBRARIES AND FORMS OF COOPERATION (in English) - MAKINEN, ILKKA (Knygotyra, 2015)
The article strives to draw parallels between the cultural contexts of the Lutheran clergy in East Prussia, where Kristijonas Donelaitis lived, and in Finland. East Prussia was part of the Prussian and Finland part of the Swedish Kingdom. The Lutheran Protestant church was state-church in both of the realms. The German culture naturally dominated in East Prussia, but its influence in Sweden and Finland was also strong. There also are parallels in the linguistic situation in East Prussia and Finland. There was a Lithuanian-speaking minority in East Prussia and a Finnish-speaking majority in Finland, both of which were shadowed by the dominant language and culture, German and Swedish, respectively. The priest served as a link between the dominant culture and administration and the common people. Two Finnish priests, Matthias Salamnius (1640–1691) and Johan Frosterus (1720–1809) that can be compared to Donelaitis in their literary production, are presented. The existence of non-theological books in the private libraries of Finnish priests is analyzed using the data in estate inventories. Information about forms of cooperation in the distribution of books, such as book circles and professional reading societies are presented in both Finland and East Prussia.